In vitro responses of human dermal fibroblasts to mechanical strain: A systematic review and meta-analysis - van Haasterecht, L.; Dsouza, C.; Ma, Y.; Korkmaz, H. I.; de Jong, Y.; Ket, J. C. F.; van Zuijlen, P. P. M.; Groot, M. L.; Komarova, S. V. (Frontiers in Mechanical Engineering, 2023)
In vitro research in the field of mechanotransducive regulation of dermal fibroblasts is characterized by highly variable methodology and contradictory results. The primary objective of this systematic review was to establish how in vitro mechanical stretch affects human dermal fibroblast function, by means of a quantitative synthesis of all available evidence. The secondary objectives were to examine the effects of covariates related to donor age, fibroblast origin, experimental treatments, and mechanical stimulation parameters on dermal fibroblast responsiveness to mechanical strain. Summary outcomes for fibroblast proliferation and collagen production were combined using a fixed-effects meta-analytical model. Subgroup analysis and meta-regression were used to investigate the effects of different conditions on the summary outcomes. Mechanical strain was found to not affect fibroblast proliferation in neonatal fibroblasts, while adult fibroblasts proliferation was significantly increased. Collagen production was significantly increased in response to mechanical stimulation, with Vitamin C stimulation as the most important covariate. Stretching frequency emerged as positively associated with fibroblast proliferation and negatively associated with collagen production. We conclude from this study that distinct differences exist in the effects of mechanical stretching between dermal fibroblasts from neonatal and adult donors, which will help to further elucidate the pathophysiological mechanism behind tension-induced scarring.